Design and construction of a flexible pharyngeal phantom (Transactions on Additive Manufacturing Meets Medicine, 2021)
Obstructive sleep apnea (OSA) is a common sleep disorder characterized by episodes of partial or complete obstruction of the upper airway during sleep. In order to experimentally examine the causes that lead to OSA, a flexible pharyngeal phantom of the upper airway geometry of an OSA patient was fabricated using additive manufacturing and silicone casting techniques. The result of each manufacturing step was recorded and examined with a control CT scan, the deviation of the phantom from the digital model was measured and evaluated.
Keywords: OSA; anatomical phantom construction; upper airway phantom